Problematic Internet Use– An introduction and current status in Nepal - Shakya, R.; Sharma, P. (Journal of Psychiatrists' Association of Nepal, 2017)
Life has become easier with the advent of internet; however excessive use of internet has created a lot of problems. Problematic internet use has been regarded as a separate clinical entity and the researches on its various aspect is on a rise all around the globe in the last decade. This condition though fairly common in Asian context too; has not seen much of recognition in clinical and research setting in Nepal. Review of the major databases has yielded four original studies in Nepal. These cross sectional studies have made an attempt to highlight the prevalence, co-morbidities and mediators to some extent. However, this doesn’t seem to be enough as compared to the literature base needed in the current scenario. Hence, we emphasize on creating awareness among public, early recognition in clinics by clinicians and further research in tertiary health care levels by researchers about this recently rising public health issue of Problematic Internet Use.